THE EQUIVALENT OF ARCHAIC WORDS IN MODERN ENGLISH A STUDY ON THE TRANSLATION OF THE LAWS AND REGULATIONS OF THE REPUBLIC OF INDONESIA - Haeza Zata Amani; Septina Indrayani; Nidia Sofa (LinguAmerta, 2024)
Archaic word is one of the major vocabulary features of legal English. The use of archaic words can be difficult to understand for non-law practitioners because they are no longer commonly used in modern English. This thesis explores the archaic words found in selected laws and regulations of the Republic of Indonesia and investigates their meaning, function, and equivalent modern word replacements and Indonesian translations. The research methodology used is descriptive-qualitative, utilizing linguistic phenomena as data, specifically archaic words. The English and Indonesian versions of Law Number 25 of 2007 on Investment, Law Number 40 of 2007 on Limited Liability Companies, Law Number 3 of 2014 on Industrial Affairs, and several government regulations related to industrial development and permits serve as the data sources. Data collection involves content analysis and Focus Group Discussions (FGD). The data are analyzed in four stages: domain, taxonomy, componential, and cultural themes. The key findings of the study reveal a total of 196 archaic words identified in the selected laws and regulations, consisting of 15 words and phrases. The most frequently encountered archaic phrase is "in the event," followed by "pursuant to," "hereinafter," and "amongst." Understanding the meaning and purpose of these archaic words is essential to comprehend their role within legal documents and facilitate the identification of modern English words or phrases that convey the same legal concepts